PENINGKATAN REGULASI EMOSI MELALUI PROGRAM HARMONY FROM WITHIN PADA REMAJA PANTI ASUHAN NARAYAN SEVA BULELENG-BALI - Puteri Handayani, Dewa Ayu; Sanjaya, Dewa Bagus; Asril, Nice Maylani; Dewantara, Putu Mas (Universitas Pendidikan Ganesha, 2022)
The psychological training and mentoring entitled â€œHarmony from Withinâ€ aimed at improving emotion regulation strategies of adolescents at the Narayan Seva Orphanage, Buleleng-Bali. Participants were 22 adolescents ranging from 16 to 20 years old. The methods included seminar, discussion, presentation, and group work. Based on the evaluation conducted, it was found this activity was rated very well by the participants. In addition, there were also differences in emotion regulation scores among the two strategies, namely cognitive reappraisal and the expressive suppression before and after training. As many as 68% of the participants experienced improvement in implementing cognitive reappraisal strategy, and only 27% of participants were finally able to minimize the implementation of expressive suppression strategy. These results showed that the training and mentoring given could provide benefits for improving cognitive reappraisal strategy, but not in minimizing expressive suppression strategy.Keywords:Â emotion regulation,Â cognitive reappraisal, expressive suppression